Issues of Reading Habits Among Malaysian Students: School and Home Perceptions - Muhammad Faizal A Ghani; Mohd Fauzan Zulkifli; Norfariza Mohd Radzi; Maszuria A. Ghani (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2021)
Abstract: The purpose of this study is to analyze issues of reading habits among school students in Malaysia. This study used a qualitative method by conducting semi-structured interviews with school leaders, teachers, and parents in urban and rural areas. Sample selection used the purposive sampling method. Criteria in selecting study participants were position, teaching experience, background related to students' reading habits, and willingness to participate in this study. The findings of this study were analyzed using thematic methods. The analysis of the issues in urban areas resulted in five (5) themes for urban areas, while there were nine (9) themes for rural areas. These themes have been arranged according to the priority of the issue. The themes of issues faced in urban areas consist of (i) Students' Attitudes and Reading Awareness, (ii) Current Reading Programs Need to Be Improved, (iii) Changes in Reading Styles and Technological Developments, (iv) Aspects of Students' Environment That Do Not Support Reading Habits and (v) No Specific Time Allocation for Reading Activities. The results of the analysis of the findings of the study with participants in rural areas consist of (i) Lack of Family Support, (ii) No facilities, (iii) Students' Attitudes and Reading Awareness, (iv) Lack of Interesting Resources and Reading Materials, (v) Limited Reading Resources, (vi) Lack of Teacher Training on Reading Practice Skills, (vii) Aspects of Students' Environment That Do Not Support Reading Habits, (viii) Current Reading Program Need Improvement, (ix) No Clear Guidelines or Profile. The results of this study can serve as a reference, especially at the stakeholder level, such as for the District Education Office, School Administrators, Non-Governmental Organizations (NGOs) as well as for policymakers who may utilize the findings of this study to identify and improve the community and students in Malaysia as a reading community.